Il GIS al servizio della sosta in ATAC a Roma - Leggeri, Flaminia; Micheli, Patrizia; Perla, Annalisa; Spagnoli, Francesca (GEOmedia, 2014)
One of the objectives of ATAC, is to provide information on public transport from her work to a wider catchment area. The mobile information services currently available are varied, the main ones are presented to users through the portal of ATAC, an aid to move around the city. With the aim of extending the information to a wider audience, in parallel to the new service aimed at users motorists to pay for parking tariffed through smartphones, mobile phones or phones, it was decided to develop a new spatial representation of the parking areas tariffed in order to offer a visually synthetic ( Blue Stripes ) . In this regard, for web pages dedicated to stopping a tariff on the website Atac, we are working to update our maps currently present withricher graphics and meaningful with the aim of facilitating the user in the planning stages of its movement, identifying clearly rates and bands applied to each staging area tariffed and giving the opportunity to view the exceptions to the tariff period, per shift and the reduced rates applicable, if one is required. Such detailed spatial representation of the affected areas will also enable Atac to perform geographicl analysis to optimize and simplify the offer to users.